(untitled) (Brazilian Journal of Radiation Sciences, 2022)
The approach taken in the WHO Guidelines for controlling radiological hazards in public water supplies has two stages. The first is an initial screening for gross alpha and beta activity to determine whether the activity concentrations are below levels at which no further action is required; and if these screening levels are exceeded, investigation of the concentration of individual radionuclides and comparison with specific guidance levels. Mineral water is obtained directly from natural sources or by extracting groundwater, it is characterized by the quantity of mineral salts, trace elements and other constituents. The bottled water industry is present in the major regions of the world, and the population consumption has increased every year in Brazil and world, also increasing new mineral water mining sites, so it is necessary to constantly check the amount of radioactivity in mineral water. The aim of this study is to quantify the concentration of the natural radionuclides in the bottled mineral water consumed in São Paulo city. The bottled mineral water samples were purchased in a supermarket in São Paulo, with 23 different brands. The determination of gross alpha and beta activity concentration in bottled mineral water by Liquid Scintillation Counting measurement was performed using a 1220 Quantulus™ Ultra Low-Level Liquid Scintillation Spectrometer. The natural radionuclides (226Ra, 228Ra, 210Pb and 40K) were measured by gamma spectrometry, using an HPGe detector. The results obtained in this study can be used for a database on bottled mineral water radioactivity from Brazil.